Effects of native biodiversity on grape loss of four castes: testing the biotic resistance hypothesis - M. Nereu; M. Nereu; R. H. Heleno; F. Lopez-Núñez; M. Agostinho; J. A. Ramos (Web Ecology, 2018)
Management of agricultural landscapes can influence the biodiversity and the ecological services provided by these ecosystems, such as natural biological pest control. Viticulture is a very important economic activity in most countries with Mediterranean climate, often shaping their landscapes and culture. Grape production is affected by a number of pests and diseases, and farmers use prophylactic and response-driven pesticides to control these pests. Here we quantified the main biotic causes of crop losses in four grape castes, two red (Touriga Nacional and Baga) and two white (Arinto and Chardonnay), and evaluated the potential effect of native biodiversity to provide biotic resistance to pest outbreaks and grape losses. Specifically, the diversity and abundance of bird and insect communities in these vineyards were quantified and divided into functional guilds (pest, neutral or auxiliary), to test whether these natural communities hold the potential to naturally control grape pests (biotic resistance hypothesis) under normal vineyard management (including pesticide application regimes). A potential association between distance to the vineyard edge and grape losses was also evaluated. We recorded a very small proportion of grape losses (mean  =  0.6 %; max  =  7.5 %), with insect pests showing a preference for the castes Baga (red) and Chardonnay (white), while bird pests avoided the caste Arinto (white). Grape color did not influence losses caused by insect pests, but birds showed a preference for red castes. The caste Baga was also more vulnerable to losses caused by fungi. Despite their low impact on grape production, most insects and birds detected in the six vineyards were pests, which entails a potentially low level of biotic resistance in this highly managed agricultural ecosystem. Further research is necessary to fully evaluate the role of functional biodiversity in vineyards, particularly if alternative production processes, such as organic farming, can increase the potential of native biodiversity to protect against grape losses from pests under lower regimes of chemical spraying.